Streamflow and lake water level changes and their attributed causes in Eastern and Southern Africa: state of the art review. Issue 6 (1st November 2016) - Schäfer, Meike Pendo; Dietrich, Ottfried; Mbilinyi, Boniface
Abstract: The objective of this review is to evaluate recent quantitative changes in streamflow and lake water levels in drainage basins of Eastern and Southern Africa. Findings indicate that the majority of analyzed case studies report decreasing streamflow or lake water levels between 1970 and 2010. The causes of change are chiefly anthropogenic, namely water withdrawal, land use and land cover change, and dams, and only to a lesser degree climate-related. However, there are distinct regional and temporal differences regarding reported changes and causes, e.g. land use and land cover change being mainly attributed to Eastern Africa, and dams to Southern Africa.